ENHANCING AMBIDEXTROUS INNOVATION THROUGH DIGITAL CAPABILITY AND KNOWLEDGE MANAGEMENT IN FLORIST SMEs - Siti Nurhasanah Putri Selayar; Hastin Umi Anisah (Adisam Publisher, 2026)
This study aims to analyze the influence of digital capability on ambidextrous innovation through knowledge management among florist SMEs in Banjarmasin. The research problem is based on the need for SMEs to adapt to digital transformation, changing consumer preferences, and increasing demands for continuous innovation. Digital capability enables business owners to utilize digital technologies in managing business activities, while knowledge management helps transform information and experience into useful knowledge for innovation. This study employed a quantitative approach using a survey method. The population consisted of active florist SME owners in Banjarmasin, with a sample of 60 respondents. Data were collected through questionnaires and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS software. The results show that digital capability has a positive and significant effect on ambidextrous innovation. Digital capability also has a positive and significant effect on knowledge management, and knowledge management has a positive and significant effect on ambidextrous innovation. Furthermore, knowledge management mediates the influence of digital capability on ambidextrous innovation. These findings indicate that digital capability can enhance ambidextrous innovation more effectively when supported by strong knowledge management practices.